TINJAUAN YURIDIS TERHADAP PEMBELAAN TERPAKSA MELAMPAUI BATAS (NOODWEER EXCES) DALAM TINDAK PIDANA PEMBUNUHAN - Tsabitah, Balqis; Razka, Muhammad Ariiq Eka Putra; Julianto, Muhammad Farhan; Rosyidah, Najwa (Zhata Institut, 2024)
Criminal law is a branch of law that regulates acts prohibited by law and prescribes punishments for the perpetrators. One important concept in criminal law is self-defense (noodweer), which provides exemption for individuals who commit crimes in defense of themselves from threats. However, in some cases, self-defense may exceed what is considered reasonable, known as noodweer exces. Noodweer exces occurs when an individual acts excessively in self-defense due to psychological pressures such as fear or panic. This study analyzes the application of noodweer exces in homicide cases. The research aims to understand the concept of noodweer exces in criminal law and how legal approaches can be applied in cases involving excessive self-defense. The research method used is a normative juridical approach through literature study. The findings indicate that the application of noodweer exces in homicide cases involves considerations of proportionality, subsidiarity, and the psychological condition of the perpetrator. By considering human rights and the emotional state of the perpetrator, the law provides room for excessive self-defense to not be subject to punishment.